Inclusive Design Strategies for Museums. Targets and Remarks for Wider Access to Culture - Sebastiano Marconcini (Ochrona Dziedzictwa Kulturowego, 2022)
Museums are repositories of culture, knowledge, and values that everyone should be able to have access to. To this end, specific attention should be paid to the issue of disability when designing or operating such facilities. Despite an increased awareness, many designers still lack a full understanding of the complexity of people's needs and the topic of inclusion. Through an excursus of the evolving concept of diversity and how design can provide an enabling or disabling built environment, this paper aims at setting the cognitive framework to address the issue of broader fruition in museum spaces. Particularly, the focus of this contribution is on the European context, its historical cities and cultural heritage. Therefore, the needs of inclusion must be balanced with those of conservation, adding an extra layer of complexity. The museum will then be examined from an inclusive perspective, highlighting the issues to be addressed and providing some suggestions on the tools available to overcome them and grant everyone access to culture.